2018
DOI: 10.1038/s41389-018-0084-0
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xl as the most promising Bcl-2 family member in targeted treatment of chondrosarcoma

Abstract: Chondrosarcomas are malignant cartilage tumors showing relative resistance to conventional chemo- and radiotherapy. Previous studies showed that chondrosarcoma cells could be sensitized to chemotherapy by inhibiting the Bcl-2 family members Bcl-2, Bcl-xl and Bcl-w using ABT-737. In this study we explored the specific role of Bcl-2 family members to identify the most important player in chondrosarcoma cell survival and chemo resistance. Immunohistochemistry was performed on tissue microarrays containing 137 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…Likewise, the synthetic lethal interaction between temozolomide and IDH mutations described in gliomas was not observed in our study [35,36]. Our research group published that the reported synthetic lethal interaction between IDH mutations and Bcl-2, NAMPT, and glutaminase inhibition was absent in chondrosarcoma [11,[37][38][39]. Together, these findings indicate that therapeutic strategies in AML and glioma based on IDH mutation status cannot be directly translated to chondrosarcoma.…”
Section: Discussionsupporting
confidence: 42%
“…Likewise, the synthetic lethal interaction between temozolomide and IDH mutations described in gliomas was not observed in our study [35,36]. Our research group published that the reported synthetic lethal interaction between IDH mutations and Bcl-2, NAMPT, and glutaminase inhibition was absent in chondrosarcoma [11,[37][38][39]. Together, these findings indicate that therapeutic strategies in AML and glioma based on IDH mutation status cannot be directly translated to chondrosarcoma.…”
Section: Discussionsupporting
confidence: 42%
“…With several cell lines where synergy was observed, the maximum synergy occurred at intermediate drug, and therefore efficacy, levels (Table 1). For instance, b B was highest at 12.5 mM cisplatin for the cell line SW1353 and at 6.25 mM cisplatin for the cell line L835 [13] (Table 1). Increasing the cisplatin level beyond this value increased efficacy but compromised synergy, reflecting the synergy-efficacy trade-off.…”
Section: Examples Of the Synergy-efficacy Trade-offmentioning
confidence: 99%
“…Finally, we present evidence of the trade-off in anticancer drugs. In a recent study, several chondrosarcoma cell lines resistant to chemotherapy were made sensitive to cisplatin by inhibiting the antiapoptotic protein Bcl-xl using the drug WEHI-539 [13]. Experiments used a fixed level of WEHI-539 and different levels of cisplatin, ranging from 0.39 to 100 mM.…”
Section: Examples Of the Synergy-efficacy Trade-offmentioning
confidence: 99%
“…The Bcl-2 family is divided into two classes, pro-apoptotic proteins and anti-apoptotic proteins; Bcl-xL is an anti-apoptotic protein, whereas Bcl-xS and Bax are pro-apoptotic proteins (32,33). Singh et al (14) showed that knockout of BC200 increased Bcl-xS protein expression, whereas Bcl-xL protein was not altered significantly.…”
Section: Discussionmentioning
confidence: 99%